Association Between Pruritus With Serum Calcium, Phosphate Levels And Ca-Po4 Product in Chronic Kidney Disease (Stage-5) Patients On Maintenance Hemodialysis - Hasan, Rafiqul; Chowdhury, Md Nizamuddin; Rahman, M Muhibur; Anwar, ASM Tanim; Wazib, Amit; Shams, Tarek; Rahman, Md Saidur; Anowar, SM Imrul; Majumder, Arifur Rahman (Journal of Dhaka Medical College, 2020)
Background: Hemodialysis is one of the treatment of end stage renal disease. Disturbance in calcium and phosphate metabolism are observed in these patients. One of the most common cutaneous manifestations in patients on hemodialysis is pruritus. The aim of this study is to evaluate the association between pruritus with serum calcium and phosphate levels in these patients. Methods: This analytic, descriptive, cross-sectional study was performed in 2014 over 191 patients of maintenance haemodialysis. Information related to the patients age, gender, residence, pruritus, duration and frequency of dialysis, was extracted from questionnaires. Serum levels of calcium, phosphate and albumin were measured & data were analyzed. Results: 68% of the patients had pruritus, of whom 48.2% had serum calcium levels below the normal range. The Mean ± SD of serum calcium, phosphate, Ca-PO4 product, and duration of dialysis were 8.77±1.22 mg/dl, 3.82±1.18 mg/dl, 34.17±12.69, and 18.01±11.94 months respectively in patients with pruritus and 9.24±1.15 mg/dl, 3.40±1.36 mg/dl, 35.75±13.02, and 17.84±16.01 months respectively in patients without pruritus. Our study showed that most patients with pruritus had serum calcium levels in the below normal range. Conclusion: Good control of serum calcium levels may have a role in reducing uraemic pruritus. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 127-133